1997
DOI: 10.1128/mcb.17.5.2468
|View full text |Cite
|
Sign up to set email alerts
|

Human Bak Induces Cell Death in Schizosaccharomyces pombe with Morphological Changes Similar to Those with Apoptosis in Mammalian Cells

Abstract: Apoptosis as a form of programmed cell death (PCD) in multicellular organisms is a well-established genetically controlled process that leads to elimination of unnecessary or damaged cells. Recently, PCD has also been described for unicellular organisms as a process for the socially advantageous regulation of cell survival. The human Bcl-2 family member Bak induces apoptosis in mammalian cells which is counteracted by the Bcl-x L protein. We show that Bak also kills the unicellular fission yeast Schizosaccharo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 44 publications
3
116
0
1
Order By: Relevance
“…Here, we successfully performed a functional analysis of five canine Bcl-2 family members in this model organism, namely the pro-apoptotic members Bak and Bax and the anti-apoptotic members Bcl-w, BclxL and Mcl-1. As previously described for the human and/or murine orthologs (Ink et al, 1997;Tao et al, 1997;Ligr et al, 1998), expression of canine Bak and Bax showed a lethal effect in yeast. Moreover, this effect was abrogated on co-expression of the anti-apoptotic members Bcl-xL, Mcl-1 and Bcl-w as previously demonstrated for large part of their human orthologs in yeast (Tao et al, 1997;Beaumont et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Here, we successfully performed a functional analysis of five canine Bcl-2 family members in this model organism, namely the pro-apoptotic members Bak and Bax and the anti-apoptotic members Bcl-w, BclxL and Mcl-1. As previously described for the human and/or murine orthologs (Ink et al, 1997;Tao et al, 1997;Ligr et al, 1998), expression of canine Bak and Bax showed a lethal effect in yeast. Moreover, this effect was abrogated on co-expression of the anti-apoptotic members Bcl-xL, Mcl-1 and Bcl-w as previously demonstrated for large part of their human orthologs in yeast (Tao et al, 1997;Beaumont et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…152 Yeast can be killed by various means such as oxidative stress, metabolic block, irradiation and other toxic substances, but cell death does not resemble apoptosis and there is no endogenous expression of known apoptosis regulators of the CED-3/caspase, CED-4 or Bcl-2/Bax families. Nevertheless, forced overexpression of Bax, Bak or CED-4 provokes vacuolarization and focal chromatin c o n d en s at i o n a s s ee n i n m am m al i an a po p t osis, 28,150,151,154,155 indicating these death factors can indeed provoke a caspase-independent form of apoptosis via components that are already present in a unicellular organism. To identify these components, a mammalian expression cDNA library has recently been screened for clones that rescue yeast from Bax-mediated cell death.…”
Section: Execution Of Caspase-independent Apoptosis: Scissor Instead mentioning
confidence: 99%
“…Transfection of yeast cells (Saccharomyces cerevisiae or Schizosaccharomyces pombe), whose entire genome is sequenced and lacks Bcl-2-like proteins, has shown that Bax and Bak clearly have a killer activity which can be neutralized by simultaneous expression of Bcl-2 or Bcl-X L (Table 4) (Ink et al, 1997;Jurgensmeier et al, 1997;Manon et al, 1997;Sato et al, 1994;Torgler et al, 1997;Zha et al, 1996a). Physical interaction between Bcl-2 and Bax is not required for the Bcl-2-mediated inhibition of Bax-induced apoptosis (Zha and Reed, 1997).…”
Section: Group Of E Ects Observation Referencesmentioning
confidence: 99%
“…Note that certain Bcl-2 homology regions (BH1 through BH4, in solid) or C-terminal hydrophobic membrane insertion sequences (tinted) are missing in determined members of the family. Some structural features (a domains) and functions determined by cristallographic or mutational analysis are indicated (Longo et al, 1997) Bcl-X L ; Mcl-1; A1 Prevent Bax/Bak-mediated killing (Manon et al, 1997;Sato et al, 1994;Tao et al, 1997) S. Pombe Bax Cell killing with chromatin condensation and vacuolization (Jurgensmeier et al, 1997) Bak Slow growth phenotype and killing with chromatic condensation and lamin dissolution (Ink et al, 1997;Jurgensmeier et al, 1997;Torgler et al, 1997) Bcl-X L , Bcl-2 Prevent Bax/Bak-mediated e ects (Jurgensmeier et al, 1997;Ink et al, 1997;Torgler et al, 1997) CED-4 Causes chromatin condenstaion and death CED-9 Prevents CED-4-induced death lular distribution of di erent members of the Bcl-2 family can depend on the cell type as well as on the family member. Thus, Bcl-2, Bcl-X L , Bax, and the Epstein ± Barr virus gene product BHRF tend to be particularly abundant in the outer mitochondrial membrane (Cory, 1995;Gonzalez-Garcia et al, 1994;Krajewski et al, 1993;Reed, 1994;Riparbelli et al, 1995;Yang and Korsmeyer, 1996;Zha et al, 1996a).…”
Section: Predominant Localization To Intracellular Membranesmentioning
confidence: 99%